Bimbingan Teknis Capacity Building bagi Stakeholder Perencana Teknis Bidang Bina Marga DPUTR Kota Madiun - Rosyid Kholilur Rohman (Universitas Merdeka Madiun, 2019)
The development of Madiun City increase in various fields included at infrastructure public. Public Works and Spatial Planning Service of Madiun city organized Â a technical assistance Â for all stakeholder in planning road in Madiun city. The stakeholder is technical staff of road division of Public Works and Spatial Planning Service of Madiun city and technical staff of engineering consultant. Aim of this technical assistance to develop their abilities in road design in order to improve output of Detail engineering and Design. The material of technical assistance such as the design of flexible pavement, the design of drainage, and design of sheet pile. In this technical assistance, Public Works and Spatial Planning Service of Madiun city joined with Engineering Faculty of Merdeka University of Madiun.Â The tutor of this technical assistance some lectures of Civil Engineering University of Merdeka Madiun.